PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA PETANI UBIKAYU DI PROVINSI LAMPUNG - Wan Abbas Zakaria; Teguh Endaryanto; Lidya Sari Mas Indah; I Rani Mellya Sari; Abdul Mutolib (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2020)
This study aims to (1) analyze the level of income and (2) analyze the factors that influence the level of household welfare of cassava farmers. The study was conducted in Gunung Agung Village, Terusan Nunyai District, Central Lampung Regency with a survey method. The sample of farmers 78 respondents was taken by proportional stratified simple random sampling. Data analysis using quantitative descriptive methods include income analysis, welfare level analysis according to BPS and Sayogyo, and using a binary logit model. The results show that the source of household income of cassava farmers is increasingly diverse and leads to off and non-farm activities. Revenue from cassava farming has decreased but is still dominant. Based on BPS and Sayogyo criteria, most cassava farming households are in a decent and prosperous life group. The factors that influence the level of welfare of cassava farmers are the amount of work, cassava farming experience, and household income.